SCREENING OF ZINGIBERACEAEPLANTS FOR ACETYLCHOLINESTERASE INHIBITORY ACTIVITY - Khairunnisa
Background and purpose: Alzheimer's Disease is characterized by the decrease of acetylcholine levels in the brain. One of the efforts to maintain the acetylcholine level areby inhibiting the acetylcholinesterase. Acetylcholinesterase (AChE) is an enzyme that converts the acetylcholine to acetate and choline. The AChE inhibitory compounds could be obtained from plants, one of the example is from the Zingiberaceae like ginger (Zingiber oficinale) and galanga (Alpiniagalanga L.). These plants has been known to have acetylcholinesterase inhibitory activity.Based on chemotaxonomic approach, plant in the same genus or tribe are expected to similiar chemical content and biological activity. This study is aimed to examine the asetilkolinesterase inhibition of severaltribal plant in Zingiberaceae family Method: Extraction was carried out by maceration using 96% ethanol for 24 hours with 2x repetitions, inhibition activity of acetylcholinesterase is measured by colorimetry approachquantitative assay (determination of total phenolic, total flavonoid, and curcuminoid content) are performed using UV-Vis spectrophotometry Results: All extracts showed acetylcholinesterase inhibitory activity with the strongest activity was given by turmeric, followed by temulawak, temu ireng, bangle, temu kunci, lempuyang and temu mangga, with IC50 74,88 ± 1,55 g/mL, 189,57±1,67 g/mL, 240,83 ±1,64 g/mL, 252,47±1,04 g/mL, 280,56±1,88 g /mL, 326,34±1,61 g/mL, and 371,63 ± 1,40 g/mL, the IC50 value of positive control (pyridostigmin) was 5,81 ±1,17 g/mL. The highest total phenolic, total flavonoid, and curcuminoid levels were given turmeric extract with total phenolic content of 435,22±0,87 mg GAE/g, total flavonoid 456,60±1,21 mg QE/g, and curcuminoids315,05±0,33 mg CE/g. Conclusion: All extracts showed acetylcholinesterase inhibitory activity with the strongest inhibition was provided by turmeric with IC50 74,88±1,55 g/mL. Tumeric extract also gave highest total phenolic content 435,22±0,87 mg GAE/g, total flavonoid content 456,60 ±1,21 mg QE/g, and curcuminoids 315,05±0,33 mg CE/g.